Neuroaxial Verses General Anesthesia for Gynecological Surgeries - Hiranand, Quratul Ain Salman, Abdul Sattar, Anum Zeb, Faheem Asghar, Shumaila Ashfaq (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To evaluate the anaesthetic effects, patient satisfaction, and the Oxidative Stress Index between neuroaxial anaesthesia (NA) and general anaesthesia (GA) during gynecologic laparoscopic surgery. Study Design: Prospective randomized study Place and Duration: Lady Reading Hospital Peshawar.1st Jan, 2021 to 30 June, 2021. Methods: The research involved ninety women between the ages of 20 and 55 who were scheduled to undergo diagnostic laparoscopy and hysteroscopy for unexplained infertility and had an ASA I-II physical status.Age, BMI and laparotomy indication were documented after obtaining informed written permission from each patient. Patients were equally divided in two groups group I received neuroaxial anesthesia and group II received general anesthesia. Post-operative outcomes among both groups were compared. SPSS 22.0 was used to analyze complete data. Results:Mean age of the patients in group I was 33.4±11.32 years and had mean BMI 25.4±7.81 kg/m2 while in group II mean age was 30.7±14.63 years with mean BMI 22.8±9.52 kg/m2. In group I 28 (62.2%) cases had ASA class I and in group II 30 (66.7%) cases had ASA class I. Diagnostic laparoscopy was majority in numbers among both groups 29 (64.4%) in group I and 26 (57.8%) in group II. Among both groups paratubal cystectomy was most common symptom found in 6 (13.3%) cases and 7 (15.6%) cases. Mean operative time in neuroaxial group was lower 45.3±6.52 minutes as compared to group II was 54.8±11.42 minutes. Mean time of anesthesia was also lower in group I as compared to group II with p value <0.003. Mean pain score was significantly reduced in group I 3.6±8.61 as compared to group II 6.8±11.92. Heart rate and arterial pressure was lower in group I. Post-operative Oxidative Stress index among patients of group II was higher 1.9±4.45 as compared to group I 0.9±0.42. Conclusion:We concluded in this study that the use of neuroaxial anesthesia undergoing gynecologica laparoscopy was effective and useful as compared to general anesthesia in terms of less pain score and oxidative stress index. Except this frequency of adverse events were also lower in neuroaxial group.